Correct the Coagulopathy and Scoop It Out: Complete Reversal of Anuric Renal Failure through the Operative Decompression of Extraperitoneal Hematoma-Induced Abdominal Compartment Syndrome - Paul B. McBeth; Michael Dunham; Chad G. Ball; Andrew W. Kirkpatrick (Case Reports in Medicine)
We report two cases of extraperitoneal compression of the intra-abdominal space resulting in abdominal compartment syndrome (ACS) with overt renal failure, which responded to operative decompression of the extra-peritoneal spaces. This discussion includes patient presentation, clinical course, diagnosis, interventions, and outcomes. Data was collected from the patient’s electronic medical record and a radiology database. ACS appears to be a rare but completely reversible complication of both retroperitoneal hematoma (RH) and rectus sheath hematoma (RSH). In patients with large RH or RSH consideration of intra-abdominal pressure (IAP) monitoring combined with aggressive operative drainage after correction of the coagulopathy should be considered. These two cases illustrate how a relatively benign pathology can result in increased IAP, organ failure, and ultimately ACS. Intervention with decompressive laparotomy and evacuation of clot resulted in return to normal physiologic function.